Biography of Abi Yacoub al-Sijistani (271_361 AH( - Shehab Ahmed, Marwa; Al–Zubaidi, Dawood Salman Khalaf (Al-Adab Journal, 2021)
The Ismaili da’wa was distinguished by its philosophical and philosophical doctrines, especially in the Islamic Mashreq, where its propagandists propagated the Ismaili doctrine in those lands and distinguished themselves with their great effort to disseminate it in a philosophical and philosophical way. They did not use intimidation, on the contrary. The Islamic Orient is one of the important regions because of its importance in the location and population, which was reflected on the political, economic and cultural reality of the Islamic world as a whole and throughout the Islamic ages. The study of one of the figures of Ismaili doctrine in the Islamic Mashreq, then known as its intellectual and propagandistic wealth, is Abu Yaqoub al-Sijistani (d. 361 AH / 971 AD), because this research is important in explaining the impact of Ismaili preachers and thinkers on intellectual life in the Islamic Mashreq.